The Correlation Between Adolescent Experiences of Violence and Parental Attachment With Adolescent Desire to Use Online Pornography - Timisela, Nancy Rosita; Elia, Heman; Mamahit, Ferry Yefta (Veritas : Jurnal Teologi dan Pelayanan, 2021)
The increasing curiosity and various hormones (particularly sexual hormones) are problems for adolescents, which frequently cause them to become unstable. Another factor that contributes to the complexity of adolescent problems is technological advances. Apart from being a useful means of information technology that is generally beneficial to human life, the internet may also become a threat to adolescents by facilitating access to explicit sexual content, namely online pornography. Besides the above factors, this research examined other factors associated with adolescents’ inclination to consume online pornography. The purpose of this study is to discover whether there is a correlation between past experiences of violence and parental attachment to the desire to use online pornography. The research method is quantitative and the research subjects were adolescents (N=167, male=70.1%, female=29.9%, M=15–19 years). The findings revealed two things: first, there was no correlation between the past experiences of violence and the desire to use online pornography (r=0.102; p>0.05); and second, parental attachment had a negative correlation with the desire to use online pornography (r=–0.157; p<0.05). The contribution of this research is to reaffirm the significance of quality adolescent-parent attachment in fostering a wholesome emotional sense of security and developing a healthy sexual identity.